Linkages between soil, crop, livestock, and human selenium status in Sub‐Saharan Africa: a scoping review. (2nd August 2022) - Mutonhodza, Beaula; Joy, Edward J. M.; Bailey, Elizabeth H.; Lark, Murray R.; Kangara, Muneta G. M.; Broadley, Martin R.; Matsungo, Tonderayi M.; Chopera, Prosper
Summary: Selenium (Se) is essential for human health, however, data on population Se status and agriculture‐nutrition‐health linkages are limited in sub‐Saharan Africa (SSA). The scoping review aims to identify linkages between Se in soils/crops, dietary Se intakes, and livestock and human Se status in SSA. Online databases, organisational websites and grey literature were used to identify articles. Articles were screened at title, abstract and full text levels using eligibility criteria. The search yielded 166 articles from which 112 were excluded during abstract screening and 54 full text articles were assessed for eligibility. The scoping review included 34 primary studies published between 1984 and 2021. The studies covered Se concentrations in soils ( n = 7), crops ( n = 9), animal tissues ( n = 2), livestock ( n = 3), and human Se status ( n = 15). The evidence showed that soil/crop Se concentrations affected Se concentration in dietary sources, dietary Se intake and biomarkers of Se status. Soil types are a primary driver of human Se status and crop Se concentration correlates positively with biomarkers of Se dietary status. Although data sets of Se concentrations exist across the food system in SSA, there is limited evidence on linkages across the agriculture‐nutrition nexus. Extensive research on Se linkages across the food chain is warranted. Abstract : Selenium linkages in Sub‐Saharan Africa.